2017
DOI: 10.1088/1478-3975/aa5a61
|View full text |Cite
|
Sign up to set email alerts
|

Modeling dynamics of mutants in heterogeneous stem cell niche

Abstract: Studying the stem cell (SC) niche architecture is a crucial step for investigating the process of oncogenesis and obtaining an effective stem cell therapy for various cancers. Recently, it has been observed that there are two groups of SCs in the SC niche collaborating with each other to maintain tissue homeostasis: border stem cells (BSCs), which are responsible in controlling the number of non-stem cells as well as stem cells, and central stem cells (CeSCs), which regulate the SC niche. Here, we develop a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The impact of migration on the role of central and border stem cells has been also studied in [ 54 ] where only a bi-compartmental structure of the stem cell niche has been used. Furthermore, Mahdipour et al [ 55 ] have considered a general multi-compartmental structure for the colonic/intestinal crypt to analyze the fixation probability and time to fixation in the crypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of migration on the role of central and border stem cells has been also studied in [ 54 ] where only a bi-compartmental structure of the stem cell niche has been used. Furthermore, Mahdipour et al [ 55 ] have considered a general multi-compartmental structure for the colonic/intestinal crypt to analyze the fixation probability and time to fixation in the crypt.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argue that stem cell symmetric division is preferred under natural selection for two-hit mutations. Furthermore, the role of migration in delaying cancer is investigated within a bi-compartmental stem cell niche [ 54 ]. A generalized multi-stage structure of the colonic/intestinal crypt has also been recruited to give an insight into the effect of subclonal heterogeneity, migration, immortality, and division polarity in carcinogenesis [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without oxygen however, the cytotoxicity of several chemotherapeutic drugs whose activity depends on generating free radicals is reduced. In addition, it has been shown that cancer stem cells (CSCs) tend to be located at the center of a solid tumor [ 152 , 153 , 154 , 155 , 156 , 157 ]. These CSCs are able to withstand lower oxygen levels than the general population of cancer cells [ 18 , 80 ].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…There are many studies that use mathematical models to explain the dynamics of tumor growth, to develop clinical responses, to identify the right therapy combination, and to overcome drug resistance in various cancer types [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Although some studies include bone modeling, osteoblast cells, or osteosarcoma treatments [ 50 , 51 , 52 , 53 , 54 ], to the best of our knowledge, there is currently no mathematical model explaining the progression of osteosarcoma tumors.…”
Section: Introductionmentioning
confidence: 99%